Television and family demography: Evidence from a natural experiment in East Germany - Sven Alfred Hartmann (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2024)
This paper examines the causal effects of television exposure on individual decisions regarding marriage, divorce, and family planning by utilizing a natural experiment in the German Democratic Republic during the period of German division. I exploit the fact that individuals in some East German areas could not receive Western television due to their place of residence before reunification in 1990. By analyzing survey data from the German Socio-Economic Panel, my results reveal that exposure to Western TV significantly reduced the likelihood of marriage and childbirth while increasing the probability of divorce among East Germans. Analyzing administrative data at the county level supports these findings. In addition, survey data from the late 1980s indicates that the observed effects are primarily due to changes in attitudes towards relationships and family life, particularly among women.
Keywords: J12; J13; L82; 330; Television; Divorce; Marriage; Fertility; East Germany; Natural experiment